2015
DOI: 10.1016/j.sjbs.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Determination of potential role of antioxidative status and circulating biochemical markers in the pathogenesis of ethambutol induced toxic optic neuropathy among diabetic and non-diabetic patients

Abstract: The present study was designed to explore the antioxidative status and circulating biochemical markers having a potential role in the pathogenesis of ethambutol (EMB) induced toxic optic neuropathy (TON) among diabetic and non-diabetic patients. Fifty patients under complete therapy of EMB for tuberculosis were included in the present study. Inclusion criteria for patients were to receive EMB everyday during treatment, a dose of 25 mg/kg for initial 2 months and 15 mg/kg during the rest of therapy period. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A similar mechanism as described above of EMB metal chelating effect has been suggested as well for its induced axonal demyelination (Guillet et al, 2010) [38]. These changes result into vascular inflammation and thus a reduced blood supply to the nerve tissue that precedes myelin breakdown (Rasool et al, 2015) [10].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A similar mechanism as described above of EMB metal chelating effect has been suggested as well for its induced axonal demyelination (Guillet et al, 2010) [38]. These changes result into vascular inflammation and thus a reduced blood supply to the nerve tissue that precedes myelin breakdown (Rasool et al, 2015) [10].…”
Section: Discussionmentioning
confidence: 55%
“…The exact mechanism of how EMB induces optic neuropathy has not been confirmed (Palomino and Martin, 2014) [9]. However it has been stipulated that it is due to the chelating effects of EMB and its metabolites that interfere with several mitochondrial metal containing enzymes (Rasool et al, 2015) [10]. This causes interruption of mitochondrial function and oxidative phosphorylation that result into optic nerve damage (Kinoshita et al, 2012) [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligodendrocytes, the major neuroglia in the optic nerve are responsible for production of myelin sheaths of the nerve fibres (Simons and Nave, 2016), which facilitates the rapid conduction of axons (Chamberlain et al, 2016) . Ethambutol induced toxic optic neuropathy is a symmetrical progressive painless condition, presenting with symptoms such as; blurring of vision, decrease in visual acuity (Rasool et al, 2015), bitemporal visual field scotoma defects, centro-caecal scotoma and disturbances in colour perception (Han et al, 2015 Although EMB toxicity is classically described as reversible on discontinuation with complete recovery over period of weeks to months (Holla et al, 2015), worsening of vision after EMB discontinuation has been observed in some patients (Garg et al, 2015). Previous studies have reported severe, and irreversible vision loss despite frequent monitoring and standard dosages (Chen, Lin, and Sheu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apart from stopping the use of EMB, there is no specific treatment available for alleviating EMB induced toxic optic neuropathy (Rasool et al, 2015). This study aimed at exploring the role of oligodendrocytes in reversing this condition by determining the effect of ethambutol toxicity on oligodendrocytes at different periods of treatment.…”
Section: Introductionmentioning
confidence: 99%